Generative Art sebagai Pembentuk Motif Geometris - Ariesa Pandanwangi; Agus Prijono; Ratnadewi Ratnadewi (Ideas Publishing, 2022)
Designing motifs is still mostly done manually, using a pencil and then drawing on paper. The purpose of this research is to offer a solution in making geometric motifs by utilizing algorithmic art produced through computer technology. This method is a combination of the use of algorithmic art and the design used in making geometric motif designs. Algorithmic Art is a subset of generative art that is the result of an algorithmic process and is designed by the artist and usually uses a random process to generate variations based on external input. The results of this study are geometric motifs using the algorithmic art method. Geometric motifs can be applied to fabrics, decorations, and others.